2013
DOI: 10.1038/onc.2013.404
|View full text |Cite
|
Sign up to set email alerts
|

HOXB13 downregulates intracellular zinc and increases NF-κB signaling to promote prostate cancer metastasis

Abstract: Characteristically, prostate cancer (PCa) cells exhibit marked decrease in intracellular zinc; however, the mechanism responsible is not clearly understood. HOXB13 is involved in PCa progression and is overexpressed in castration-resistant PCa. DNA microarray analysis of LNCaP Pca cells showed that ZnT zinc output transporters were strikingly upregulated among androgen-independent HOXB13 target genes. Furthermore, exogenous HOXB13 caused intracellular zinc concentrations to fall in PCa cells, stimulated NF-κB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 41 publications
3
58
0
Order By: Relevance
“…Heijmink et al [72] showed that citrate is absent in lymph node metastasis; and this would be indicative of decreased zinc. Kim et al [73] reported that promotion of prostate cancer invasion and metastasis occurs by decreasing intracellular zinc levels. Compelling evidence is also provided by identification of the loss of citrate, zinc, and ZIP1 in the metastatic lymph nodes in TRAMP.…”
Section: Zinc For the Treatment Of Zip1-deficient Prostate Cancermentioning
confidence: 99%
“…Heijmink et al [72] showed that citrate is absent in lymph node metastasis; and this would be indicative of decreased zinc. Kim et al [73] reported that promotion of prostate cancer invasion and metastasis occurs by decreasing intracellular zinc levels. Compelling evidence is also provided by identification of the loss of citrate, zinc, and ZIP1 in the metastatic lymph nodes in TRAMP.…”
Section: Zinc For the Treatment Of Zip1-deficient Prostate Cancermentioning
confidence: 99%
“…Although zinc-transporter 1 might be a target for therapy, currently no drug exists to activate this transporter [123]. Additionally, a low zinc level might be maintained in later stages by HoxB13-mediated induction of the zinc output transporter ZnT4 [186].…”
Section: Genetic Drivers Signaling and Microenvironment In Prostate mentioning
confidence: 99%
“…A further pro-oncogenic effect of HOXB13 is exerted through the upregulation of zinc transporters that in turn results in lower intracellular zinc concentrations. This reduces the level of inhibitor of NF-κΒ alpha (IκΒα) and promotes NF-κΒα signaling leading to increased invasion and metastasis [52] . Thus, HOXB13 exerts multiple tumor-promoting effects through the regulation of specific target genes.…”
Section: Hox Genes In Prostate Cancermentioning
confidence: 99%